2018
DOI: 10.5610/jaee.18.3_15
|View full text |Cite
|
Sign up to set email alerts
|

Change of Natural Frequency of Low-Rise Buildings Based on Long-Term Vibration Records

Abstract: This paper aims to describe the changes in the dynamic characteristics of two existing buildings in Miyagi Pref., Japan. One is a reinforced-concrete(RC) structure and the other is steel one. In this study, we found that the natural frequency of the RC structure is more strongly correlated with temperature in comparison with the steel structure. The temperature dependence of the natural frequencies is included in record indicating the amplitude dependence of the building's dynamic characteristics, and correcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Figure 3 also shows the 10-day averages of temperature 14) at the Japan Meteorological Agency (JMA) Edogawa seaside station (approximately 7 km east-southeast of the subject structure), indicating that the natural period tends to shorten as the average temperature increases. Therefore, the same trend was observed in these buildings as in previous studies 1), 3) . The graphs on the right side of Fig.…”
Section: Change Over Time Of Natural Period Of Each Building Using Lo...supporting
confidence: 90%
See 1 more Smart Citation
“…Figure 3 also shows the 10-day averages of temperature 14) at the Japan Meteorological Agency (JMA) Edogawa seaside station (approximately 7 km east-southeast of the subject structure), indicating that the natural period tends to shorten as the average temperature increases. Therefore, the same trend was observed in these buildings as in previous studies 1), 3) . The graphs on the right side of Fig.…”
Section: Change Over Time Of Natural Period Of Each Building Using Lo...supporting
confidence: 90%
“…The use of microtremors allows continuous monitoring of changes in the vibration characteristics of the structure. For example, Okamoto et al 1) and Hatayama et al 3) monitored a super high-rise steel structure building and a three-story steel structure building, respectively, using microtremor and seismic records. They reported that the natural frequencies showed seasonal variations and that there was a positive correlation between the natural frequencies and air temperature.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Guillier et al (2016) found that the natural frequency of a 3.5-story reinforced concrete (RC) building may increase due to increase in temperature up to about 3.5%. Hatakeyama et al (2018) compared such variations for 3-story RC and steel buildings and found that, for the steel building, the variations were much smaller than those for the RC building. We note that the temperature effects occur concurrently with the operational conditions, such as the amplitude of response, and with other weather conditions, such as humidity and rainfall, and may be difficult to separate reliably.…”
Section: Thermal Effectsmentioning
confidence: 99%
“…The operating conditions include, for example, the amplitude of the response, with the mechanism of the effect being the nonlinear elastic behavior of the structure, soil, and soil-structure system, such as opening and closing of cracks in concrete, softening of the soil, and effective lengthening of the structure caused by the formation of gaps between the foundation and the soil (Ebrahimian et al, 2017;Kashima, 2017;Trifunac et al, 2001aTrifunac et al, , 2001bUdwadia and Trifunac, 1973). The environmental conditions include, for example, the air temperature, humidity, and heavy rainfall, which may affect the properties of the structural material and structural system, and the properties of the soil and the soil-foundation-structure system (Clinton et al, 2006;Guillier et al, 2016;Han et al, 2021;Hatakeyama et al, 2018;Herak and Herak, 2010;Ramı´rez et al, 2022;Todorovska and Al Rjoub, 2006;Yuen and Kuok, 2010). The effects of these conditions on the damage-sensitive parameters may be possible to eliminate or reduce in the future by developing reliable predictive models and methods for correction.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the changes of dynamic properties (eg., natural frequencies) of structures under the ground motion can indicate potential damages or deterioration of structural components. However, natural frequencies are easily to be wandering by environmental factors, such as temperature [1]. Seismic response of buildings can be regarded as wave propagation in the vertical direction.…”
Section: Introductionmentioning
confidence: 99%